Gamestop Investors as an Eng(r)aged Digital Public - Yang, Misti; Lee, Christopher (Javnost-The Public, 2023)
The trading app Robinhood proclaims to be “on a mission to democratise finance for all,” but, during the GameStop Revolution of January 2021, Robinhood prohibited its users from selling GME. For a vocal group of users, this restricted access revealed that Robinhood’s democratising mission was a farce, and they took to Reddit to critique the company’s actions. Subsequent regulatory hearings were held, including a series by the U.S. House Committee on Financial Services that included testimony from the CEOs of both Robinhood and Reddit. We contend that participants’ arguments reflect rhetorical strategies used by technological innovators, users, and the institutions that regulate them to manage public engagement in the name of “democracy.” Using discourse from CEOs, policy makers, and redditors, we suggest that understanding the GameStop Revolution as a crisis of public engagement helps to theorise how digital publics form, how they are engaged, and how they negotiate public access and input into online infrastructures. We argue that Congressional testimony reflects critical digital publics that are necessary prerequisites for democratising digital infrastructure. While these arguments centre on the economic and the digital universe, we suggest that the insights can inform broader questions about public engagement.